The Use of Modern Technology for Rural Industrialization and Its Implications on the Rural SMEs Economic Growth - LEKHANYA, Lawrence Mpele (Journal of Economics and Behavioral Studies, 2019)
Hence technology delivery is perceived to be an essential catalyst for rural development. This paper intends to present an empirical study on the use of modern technology for rural industrialization and its theoretical and practical implication on the rural SMEs economic growth. The idea of rural industrialization and how it can enhance the rural SMEs economic growth still the issue of concern of many policy-makers. The study seeks to establish understanding, knowledge and awareness about how the use of modern technology would assist in building strong rural industrialization that will have a positive change in the rural SMEs economy. In this research 127 participants consist with business managers/owners running SMEs in the province of KwaZulu-Natal were chosen for empirical data collection from both South and Northern parts of the Province. SPSS (24.0) version was used for the analysis of data. A quantitative questionnaire was used and distributed to the respondents. The findings revealed that in many cases there is no specific rural industrialization policy does not exist or somehow fall short, government attitudes towards rural industrialization as well as rural infrastructure development were also identified by respondents as areas of concern for rural industrialization. The exploratory and quantitative nature limited the survey. Hence, the application of this result should be made with utmost care. Further investigation which may include large and other parts of the country is therefore recommended.